As(III) adsorption onto Fe-impregnated food waste biochar: experimental investigation, modeling, and optimization using response surface methodology - Lyonga, Fritz Ndumbe; Hong, Seung Hee; Cho, Eun Ji; Kang, Jin Kyu; Lee, Chang Gu; Park, Seong Jik (Environmental Geochemistry and Health, 2021)
Biochar derived from food waste was modified with Fe to enhance its adsorption capacity for As(III), which is the most toxic form of As. The synthesis of Fe-impregnated food waste biochar (Fe-FWB) was optimized using response surface methodology (RSM), and the pyrolysis time (1.0, 2.5, and 4.0 h), temperature (300, 450, and 600 °C), and Fe concentration (0.1, 0.3, and 0.5 M) were set as independent variables. The pyrolysis temperature and Fe concentration significantly influenced the As(III) removal, but the effect of pyrolysis time was insignificant. The optimum conditions for the synthesis of Fe-FWB were 1 h and 300 °C with a 0.42-M Fe concentration. Both physical and chemical properties of the optimized Fe-FWB were studied. They were also used for kinetic, equilibrium, thermodynamic, pH, and competing anion studies. Kinetic adsorption experiments demonstrated that the pseudo-second-order model had a superior fit for As(III) adsorption than the pseudo-first-order model. The maximum adsorption capacity derived from the Langmuir model was 119.5 mg/g, which surpassed that of other adsorbents published in the literature. Maximum As(III) adsorption occurred at an elevated pH in the range from 3 to 11 owing to the presence of As(III) as H2AsO3− above a pH of 9.2. A slight reduction in As(III) adsorption was observed in the existence of bicarbonate, hydrogen phosphate, nitrate, and sulfate even at a high concentration of 10 mM. This study demonstrates that aqueous solutions can be treated using Fe-FWB, which is an affordable and readily available resource for As(III) removal.
Keywords: Adsorption; Charcoal; Food; Hydrogen-Ion Concentration; Kinetics; Refuse Disposal; Water Pollutants, Chemical; Adsorption; As(III); Fe impregnation; Food waste biochar; Response surface methodology